Covid y embarazo. punto de vista inmunológico, clínico y repercusiones materno fetales. - Salinas Quito, Nathaly Elizabeth (Machala : Universidad Técnica de Machala, 2020)
ABSTRACT Currently, humanity is witnessing the emergence of a new pandemic; the WHO, designated it Covid-19 caused by the Coronavirus Acute Respiratory Syndrome type 2 virus (SARS-CoV-2). This has generated concern especially among vulnerable groups such as pregnant women and the mother-child pair. Objective: To describe immunological and clinical aspects and the maternal-fetal repercussions in pregnant women with Covid-19 that can be used for a correct approach in primary health care. Material and Methods: Retrospective study, in sources such as Pubmed, Google Academic, Trip medical database, Cochrane, the lancet, of the last 5 years in relation to the subject. Results: 44 bibliographies were used, 10 correspond to immunology of normal pregnancy, 13 to covid alterations in gestation, 9 to clinical manifestations and 8 to complications. Conclusion: The unexpected panorama of the covid 19 pandemic, has generated diverse worries and challenges to the scientific community, which tries to reveal the immunological aspects, taking into account that the immunological state of a pregnant woman differs from the rest of the population. The reported studies mention that pregnant women present the same clinical manifestations as the rest of the population; it remains to be clarified that there are vertical transmission mechanisms and that it could generate serious repercussions in the mother-child binomial. It is essential to continue the search for more scientific information provided by researchers, in order to focus it on primary health care.
En la actualidad, la humanidad está siendo testigo del surgimiento de una nueva pandemia; la OMS, la designó Covid-19 ocasionada por el virus Síndrome Respiratorio Agudo por Coronavirus tipo 2 (SARS-CoV-2). Lo que ha generado preocupación sobre todo en grupos vulnerables como las mujeres en estado de gestación y en el binomio Madre- hijo. Objetivo: Describir aspectos inmunológicos, clínicos, y repercusiones materno-fetales en mujeres embarazadas con Covid-19 que sirvan para un correcto abordaje en atención primaria en salud. Material y Métodos: Estudio retrospectivo, en fuentes como Pubmed, Google Académico, Trip medical database, Cochrane, the lancet, de los últimos 5 años en relación a la temática. Resultados: Se utilizó 44 bibliografías, 10 corresponden a inmunología del embarazo normal, 13 a las alteraciones del covid en la gestación, 9 a las manifestaciones clínicas y 8 a las complicaciones. Conclusión: El panorama imprevisto de la pandemia de covid 19, ha generado diversas inquietudes y desafíos a la comunidad científica, que trata de desvelar los aspectos inmunológicos, teniendo en cuenta que el estado inmunológico de una mujer gestante difiere al del resto de la población. Los estudios reportados mencionan que la mujer embarazada presenta las mismas manifestaciones clínicas que el resto de la población; faltando por aclarar que existen mecanismo de transmisión vertical y que podría generar graves repercusiones en el binomio madre- hijo. Es imprescindible continuar en la búsqueda de mayor información científica que proporcionen los investigadores, a fin de enfocarlo en la atención primaria de salud.
Keywords: INMUNOLOGIA DEL EMBARAZO; COVID-19